Physicochemical Characterization and Development of a Microemulsion System for Transdermal Use - Silva, Jose A.; Bedor, Danilo C. G.; Damasceno, Bolivar P. G. L.; Oliveira, Anselmo Gomes de [UNESP]; Egito, E. Socrates T.; Santana, Davi P. (Taylor & Francis Inc, 2010)
A microemulsion (ME) carrier system containing diclofenac diethylamine (DDA) was developed and physicochemically characterized. In addition, a methodology for analytical determination of DDA by UV-Vis spectrophotometry was validated. The methodology used to produce the ME was simple and reliable, producing a stable ME system with a high DDA entrapment efficiency of 89.6 +/- 14.19%. The ME system presents a mean droplet size, conductivity, pH, refractive index and viscosity of around 50 nm, 300 mu S cm(-1), 7.0, 1.399, and 110 mPa, respectively. Furthermore, the analytical method developed to evaluate the DDA content was validated and used to quantify DDA in the ME formulations.
Keywords: Diclofenac diethylamine; microemulsion; pseudo-ternary phase-diagram; spectrophotometry; stability; validation